LITERACY THROUGH THE SOCIOLINGUISTIC METHOD - Maria da Silva Siqueira, Antonia; Siqueira dos Santos, José; de Lourdes Andrade Jovial Macarini, Sandra (Revista Gênero e Interdisciplinaridade, 2026)
The sociolinguistic method emerges as an alternative to traditional literacy and language teaching models—considering language as a social and variable practice. Grounded in Sociolinguistics studies, especially those of William Labov, it values linguistic diversity and seeks to bring teaching closer to the cultural reality of students. The central proposal is to promote literate literacy, that is, to teach reading and writing without disregarding orality and the linguistic varieties present in students’ daily lives, recognizing that different ways of speaking and writing are legitimate and can be used as a starting point for learning. Research shows that its application contributes to reducing school failure in literacy, promoting social inclusion and respect for linguistic identities, and encouraging culturally sensitive pedagogical practices.